Serum Vitamin D Metabolites and CXCL10 Concentrations Associate With Survival in Dogs With Immune Mediated Disease - Mick, Phillip J.; Peng, Seth A.; Loftus, John P. (Frontiers in Veterinary Science, 2019)
Background – Low vitamin D increases the risk of immune-mediated disease (IMD) in human beings and rodent models. Vitamin D metabolites, particularly 1,25(OH)2D3, modulate gene expression of immune cells and may attenuate immune pathways that drive IMD. Hypothesis/Objectives – Our primary hypothesis was that serum 25(OH)D3 and 1,25(OH)2D3, are reduced in patients with IMD and associate with poorer outcomes. We secondarily hypothesized serum 24,25(OH)2D3 would not be associated with disease or outcome. We also measured serum CXCL10 concentrations to determine if an increase occurs in dogs with IMD and in association with poorer survival. Animals – We enrolled dogs diagnosed with IMD (n=29) and healthy control dogs (n=9) in the study with informed client consent. Methods – Serum was collected and stored at -80ºC until analyses. Serum vitamin D metabolites were measured by LC-MS/MS by an accredited laboratory. A commercially available canine-specific ELISA kit measured serum CXCL10. Results – Serum 25(OH)D3 and 1,25(OH)2D3 were significantly reduced in dogs (n=25) with IMD. Serum CXCL10 concentrations were 30 times higher in dogs (n=25) with IMD than controls (P = 0.004). The median survival time (MST) for dogs with 25(OH)D3 concentrations </= the median was 106 days, while dogs with concentrations of 25(OH)D3 > the median did not achieve an MST. Conclusions and clinical importance – Serum 25(OH)D3 and 1,25(OH)2D3, but not 24,25(OH)2D3 levels are reduced dogs with IMD. Vitamin D metabolites and CXCL10 may be useful prognostic markers and may be targets for adjunct therapy in canine IMD. These data support the future investigation of vitamin D analogs in the treatment of canine IMD.